CSRS vs CPA: Dilema Mahasiswa Akuntansi Menentukan Pilihan Kariernya - Fransbosly Parulian Panggabean; Anton Arisman (Universitas Multi Data Palembang, 2026)
This study aims to examine the dilemma faced by accounting students in choosing between the Certified Sustainability Reporting Specialist (CSRS) and Certified Public Accountant (CPA) career paths, influenced by external and internal factors. The scope of this research includes job market considerations and work environment as external factors, as well as economic motivation and career motivation as internal factors. A quantitative approach with a correlational research design was employed. Data were collected through questionnaires from 103 accounting students in Palembang City and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that job market considerations have a significant effect on students’ interest in pursuing both CSRS and CPA certifications. Motivation significantly influences interest in obtaining the CSRS certification but does not have a significant effect on interest in the CPA certification. The findings conclude that accounting students’ career choice dilemma is formed through the interaction of external and internal factors, as explained by the Theory of Planned Behavior.